Getting Through COVID-19: The Pandemic’s Impact on the Psychology of Sustainability, Quality of Life, and the Global Economy – A Systematic Review - El Keshky, Mogeda El Sayed; Basyouni, Sawzan Sadaqa; Al Sabban, Abeer Mohammad (Frontiers in Psychology, 2020)
The COVID-19 pandemic may affect the world severely in terms of quality of life, political, environmental, and economic sustainable development, and the global economy. Its impact is attested to by the number of research studies on it. The main aim of this study is to evaluate the impact of COVID-19 on the psychology of sustainability (quality of life), on sustainable development, and on the global economy. A computerized literature search was performed, and journal articles from authentic sources were extracted, including MEDLINE (PubMed), Google Scholar, Science Direct, ProQuest, and Emerald Insight. The references in selected articles were screened to identify any relevant studies. The following inclusion criteria were followed: research articles based on the COVID-19 pandemic, and articles, research papers, journals, and news articles published 2010 to 2020. The exclusion criteria were as follow: psychology research, articles, and journals published before 2010 and research articles having no link with the current pandemic’s impact on the psychology of sustainability, quality of life, and the global economy. Of the initial 350 articles identified, only 61 studies were found to be relevant and meet the inclusion criteria. Based on these articles, the review highlights that compared to developed countries, the developing nations and poor nations such as African countries with compromised health structures have been greatly affected. There are close associations between health, economic, environmental, and political issues globally. The pandemic can be managed if we follow new policies that implement economic and public health changes worldwide. A planned, coordinated approach between the public-private sector is required, designed according to each country’s health system and economy. We can come out of this crisis if we work together and support both developed and developing nations.